Estimating Career Benefits from Online Community Leadership: Evidence from Stack Exchange Moderators - Forderer, Jens; Burtch, Gordon (Management Science, 2025)
Many IT professionals seek to improve their job prospects by engaging as leaders of online communities, for example, by serving as a moderator or admin. We investigate whether such community leadership leads to (causal) improvements in individuals’ careers. We assemble a data set, including job histories of IT professionals who have sought election as moderators (mods) in Stack Exchange question-and-answer communities, between 2010 and 2020. We estimate the career benefits of moderatorship under two complementary identification strategies: difference-in-differences (DID) and regression discontinuity (RD). We observe qualitatively consistent results under each design, finding that election to a moderator role has a significant, causal, positive effect on job mobility. We estimate that moderatorship increases the probability of a job change by between 4.7 and 12.3 percentage points over the two years following the election. We also report a series of secondary analyses that speak to associated salary increases and show evidence consistent with the notion that social capital and signaling play a role. Our findings help us understand the benefits of online community leadership, and they extend our understanding of the motivations for online community engagement. This paper was accepted by Chris Forman, information systems. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2019.03252 .